Association between the triglyceride to high density lipoprotein cholesterol ratio and the incidence of metabolic dysfunction-associated fatty liver disease: a retrospective cohort study - Xiangming Ma; Jianguo Jia; Haozhe Cui; Jing Zhou; Fei Tian; Jingtao Yang; Yali Zhang; Jiaying Dai; Liying Cao (BMC Gastroenterology)
Abstract Background The triglyceride to high density lipoprotein cholesterol ratio (TG/HDL-C) is a confirmed predictive factor for insulin resistance and is suggested to be closely related to metabolic dysfunction-associated fatty liver disease (MAFLD), but previous research is inconclusive. The association between TG/HDL-C and MAFLD incidence was further explored in this large-sample, long-term retrospective cohort study. Methods Individuals who participated in the Kailuan Group health examination from July 2006 to December 2007 (n = 49,518) were included. Data from anthropometric and biochemical indices, epidemiological surveys, and liver ultrasound examinations were collected and analysed statistically, focusing on the association between TG/HDL-C and the incidence of MAFLD. Results During a mean follow-up period of 7.62 ± 3.99 years, 24,838 participants developed MAFLD. The cumulative MAFLD incidence rates associated with the first to fourth quartiles of TG/HDL-C were 59.16%, 65.04%, 71.27%, and 79.28%, respectively. The multivariate Cox proportional hazards regression model revealed that the hazard ratios (HRs) (95% CIs) for MAFLD in the second, third, and fourth quartiles were 1.20 (1.16–1.25), 1.50 (1.45–1.56), and 2.02 (1.95–2.10) (P for trend < 0.05), respectively, and the HR (95% CI) corresponding to an increase of one standard deviation in TG/HDL-C was 1.10 (1.09–1.11) (P < 0.05). Subsequent subgroup and sensitivity analyses yielded results similar to those of the main analyses. Conclusions TG/HDL-C is independently associated with MAFLD risk, with higher TG/HDL-C indicating greater MAFLD risk.